2019
DOI: 10.1007/s40200-019-00417-y
|View full text |Cite
|
Sign up to set email alerts
|

Determining minimum set of features for diabetes mobile apps

Abstract: Purpose Interest in mobile health applications (apps) for diabetes self-care is growing. Mobile health is a promising new treatment modality for diabetes, though few smartphone apps have been designed based on a proper study and prioritization. The aim of this study was to determine a minimum set of features for diabetes mobile apps. Methods This study was conducted in three steps: 1.A review of the literature to collect all available features, 2. Assessing the validity of suggested features by Content Validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…Despite best efforts, limited medical resources and time make it difficult to educate patients and meet their individual needs in traditional face-to-face interventions [ 50 ]. The advantage of the mHealth service comes from its high scalability for providing services, for example, disseminating a large amount of educational material to a wide range of patients with hypertension for effective health education for chronic disease management [ 51 - 53 ]. It also allows these patients to absorb the information in their own time and at their own pace until they are fully aware of the importance and have the ability to perform self-management.…”
Section: Discussionmentioning
confidence: 99%
“…Despite best efforts, limited medical resources and time make it difficult to educate patients and meet their individual needs in traditional face-to-face interventions [ 50 ]. The advantage of the mHealth service comes from its high scalability for providing services, for example, disseminating a large amount of educational material to a wide range of patients with hypertension for effective health education for chronic disease management [ 51 - 53 ]. It also allows these patients to absorb the information in their own time and at their own pace until they are fully aware of the importance and have the ability to perform self-management.…”
Section: Discussionmentioning
confidence: 99%
“…The details of methods and results of the literature review as well as the process of selecting and verifying the features were published previously [ 22 ]. Based on expert opinions, 23 relevant features out of 33 were approved.…”
Section: Resultsmentioning
confidence: 99%
“…People with diabetes themselves also acknowledge the concerns of using these apps, which may be related to their experiences of using unreliable online tools. This is a reasonable concern because few apps are research-based and even may be developed without any guideline-based or expert-approved content [ 22 ]. The results of this study showed that users were generally satisfied with the app.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations